The Cognitive Levels in Reading Comprehension Questions: A Bloom’s Taxonomy Study of The Grade 8 English for Nusantara Textbook in The Indonesian EFL Context. - Ekalia, Yulian Juita; Jemadi, Fransiskus; Beda, Raimundus; Neldis, Skolastika (ITScience (Information Technology and Science), 2025)
This study aimed to examine the cognitive levels of reading comprehension questions in the English for Nusantara Grade 8 textbook using Bloom’s Revised Taxonomy. Specifically, it sought to identify the extent to which the textbook promotes lower-order and higher-order thinking skills (LOTS and HOTS) through its reading comprehension tasks. A qualitative content analysis was conducted on 190 reading comprehension questions extracted from five textbook chapters and one progress check section. Each question was categorized according to the six cognitive levels outlined in Bloom’s Revised Taxonomy: Remembering, Understanding, Applying, Analyzing, Evaluating, and Creating. Frequencies and percentages were calculated to determine the distribution of cognitive levels across chapters. The findings revealed a predominant emphasis on lower order thinking skills, with Understanding and Remembering accounting for most questions in all sections. Higher-order thinking skills were considerably underrepresented, particularly Applying (2.11%) and Creating (3.16%). The progress check section assessed only Remembering and Understanding, indicating minimal cognitive challenge. While Chapter 4 demonstrated a more balanced cognitive distribution, the overall results reflect a narrow scope of cognitive engagement. In conclusion, this study contributes to the growing body of research on textbook evaluation in EFL contexts by highlighting the imbalance in cognitive demand of reading comprehension questions. It requires the need for instructional materials and assessment practices to be reoriented toward fostering critical, analytical, and creative thinking skills among learners.